Scrum : novice to ninja - Green, M. David (Sitepoint, 2016)
Scrum is the most popular agile project management methodology used in web projects today. While most Scrum books tend to be lengthy textbooks that cover every detail of Scrum for all types of organizations, this highly practical book concentrates solely on how best to apply Scrum in web and mobile development projects.
Keywords: Scrum (Computer software development); Agile software development; Web applications; Mobile apps; Project management : Data processing; ketterät menetelmät; ohjelmistokehitys; projektinhallinta; tiimit; verkkoympäristö; mobiilisovellukset